Regorafenib combined with sintilimab as second-line treatment for advanced HCC patient: a case report - Wan, Yanzhi; Zhu, Hong (Frontiers in Oncology, 2023)
Hepatocellular carcinoma (HCC) is a tumor with a high degree of malignancy. Patients have poor outcomes and short survival times, especially after progression to first-line systemic therapy. Regorafenib is the standard second-line treatment for HCC, but there is no conclusive evidence that regorafenib combined with immunotherapy can be used as a second-line treatment. We present the case of a 50-year-old man with a chronic hepatitis B (CHB) infection for more than 30 years who was diagnosed with stage Barcelona Clinic Liver Cancer (BCLC)-B hepatocellular carcinoma. Unfortunately, recurrence and metastasis occurred soon after radical surgery and standard first-line treatment with lenvatinib. The patient was then treated with regorafenib plus sintilimab as second-line treatment. Surprisingly, soon after treatment, the patient reached a state of partial response (PR) that lasted for more than one year, which is currently close to that of complete response (CR). Regorafenib combined sintilimab as second-line treatment showed an excellent curative effect in this patient, who had HCC with multiple metastases to the liver and lungs. This treatment, which has tolerable side effects, enabled the patient to reach a state of PR that lasted over one year, which is currently close to CR. Therefore, it may be a potential second-line treatment strategy.